Agrarian Policy of the Region in Terms of Economic Development Innovation - Reznichenko, Sergey M.; Vasilieva, Nadezhda K.; Shichiyakh, Rustem A.; Medvedeva, Yulia M.; Mindlin, Yurii B. (International Journal of Economics and Financial Issues, 2016)
One of actual problems of regional economies is the problem of the transition of inter-regional divergence and problematic regions to the model of “catching up” development, definition of the newest competitive domestic and world market, forms of development of the agrarian policy of the regional territories of the state. Being a successful model of public-private partnerships and interaction between businesses, agro-industrial innovative education economic level represents the source of competitiveness of the region increases its level of importance and implementation of global processes in the agricultural sector. The cluster campaign of agrarian policy created on the account of affirmative synergy effects of regional agglomeration, network effects, diffusion of innovations, able to act as an accelerator of socio-economic education development stagnated production processes of problem regions, prevent deprivation in rural areas. Plan for the development of agro-industrial economic cluster and the program of its implementation with the implementation of the comprehensive state support of innovative initiatives and education clustered development in regional areas. Thus, the imperative of ensuring the unity of economic space establishes the need for modernization of program target management of socio-economic development of problem regions, in rural areas the formation of cluster strategies and network models of cooperation in agro-industrial complex. Keywords: innovation, economy, region, competition, cluster, complex, state JEL Classifications: J43, O13, Q13, Q19